The Effect of Employee Job Satisfaction, Career Development, and Organizational Culture on Employee Retention at PT Pupuk Sriwidjaja Palembang - Nulidya, Octy; Azwardi; Cahyadi, Afriyadi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of job satisfaction, career development, and organizational culture on employee retention at PT Pupuk Sriwidjaja Palembang. Using a causal quantitative approach based on Social Exchange Theory, data were collected from 243 Millennial and Gen Z employees and analyzed using multiple linear regression. The results indicate that job satisfaction and organizational culture have positive and significant effects on employee retention, while career development is not significant in the multivariate model. Simultaneously, the three variables significantly explain 73.1% of retention variance. The findings imply that employee retention strategies should integrate satisfaction, culture, and transparent career management.